UPAYA MENINGKATKAN MOTORIK HALUS ANAK USIA DINI MELALUI KEGIATAN MENGANYAM MENGGUNAKAN MEDIA LOOSE PART DI RA AL-HIKMAH - Hijjah Shintiya Shani; Amat Hidayat; Ratu Yustika Rini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to improve fine motor skills in early childhood through weaving activities using loose part media at RA Al-Hikmah. The research method applied is descriptive qualitative, employing observation, interview, and documentation techniques for data collection. The research subjects consisted of one teacher and seven children aged 5–6 years from group B. The results revealed that weaving activities using loose part materials significantly enhance children’s hand–eye coordination, accuracy, and finger dexterity. Furthermore, this activity fostered children’s interest, creativity, and independence in learning. Therefore, the use of loose parts media proved effective in developing fine motor skills in early childhood within an engaging learning environment.